Body Image and Quality of Life and Brace Wear Adherence in Females With Adolescent Idiopathic Scoliosis. Issue 8 (December 2017) - Schwieger, Traci; Campo, Shelly; Weinstein, Stuart L.; Dolan, Lori A.; Ashida, Sato; Steuber, Keli R.
Abstract : Background: Clinical evidence regarding the ability of braces to decrease the risk of curve progression to surgical threshold in patients with adolescent idiopathic scoliosis (AIS) continues to strengthen. Unfortunately, there is still a great deal of uncertainty regarding the impact of brace wear on psychosocial well-being or the impact of psychological well-being on brace wear adherence. The purpose of this study is to evaluate psychosocial well-being, in particular body image and quality of life (QOL), and brace wear adherence in female AIS patients undergoing brace treatment. Methods: The Bracing in Adolescent Idiopathic Scoliosis Trial (BrAIST) was a multicenter, controlled trial using randomized and preference assignments into an observation or brace treatment group. BrAIST patients were skeletally immature adolescents diagnosed with AIS having moderate curve sizes (20 to 40 degrees). Patients in the bracing group were instructed to wear a thoracolumbosacral orthosis, at least 18 h/d. Scores on the Spinal Appearance Questionnaire and the PedsQL4.0 Generic Scales from 167 female BrAIST patients who were randomized to brace treatment (n=58) and patients who chose brace treatment (n=109) were analyzed. Results: At baseline and at 12 months, no differences were found between the least-adherent brace wear group (<6 h/d) and most-adherent brace wear group (≥12 h/d) patients in terms of major curve, body image, and QOL. In the most-adherent group, poorer body image scores were significantly correlated with poorer QOL scores at baseline, at 6 months, and at 12 months but not at 18 months. In general, body image scores and QOL scores were not significantly correlated in the least-adherent group. When comparing patients that had a ≥6 degree increase of their major curve between baseline and 12 months to patients that did not, there were no significant differences in body image or QOL scores. Conclusions: For females adolescents with AIS, body image and QOL do not have a significant impact on brace wear adherence and are subsequently not significantly impacted by brace wear. Level of Evidence: Level II—therapeutic (prospective comparative study).